1992
DOI: 10.1029/91wr03099
|View full text |Cite
|
Sign up to set email alerts
|

Spatial averaging of transmissivity in heterogeneous fields with flow toward a well

Abstract: Steady state nonuniform flow in a heterogeneous medium is investigated using a combined numerical-empirical approach. The objective of the study is to determine the effective transmissivity of a square field with a constant-head external boundary and a constant-rate well at its center. Transmissivity at the point scale is modeled as an isotropic and multivariate lognormal spatial random function. Block transmissivities are defined using an empirical scaling up of point support values within the field. The scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 20 publications
(16 reference statements)
5
79
0
Order By: Relevance
“…Consistent with Matheron they found that for fixed Ao, k, increases toward as .,/Ao + 0, and decreases and (4) asymptotically approaches F: @e., ensemble harmonic average of ko(X)) as .,/Ao + w . For similar flow conditions, Desbarats (1992b) modeled Le as a weighted spatial geometric average where the log permeabilities were weighed by the inverse square of their distance from the well.…”
Section: Model Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with Matheron they found that for fixed Ao, k, increases toward as .,/Ao + 0, and decreases and (4) asymptotically approaches F: @e., ensemble harmonic average of ko(X)) as .,/Ao + w . For similar flow conditions, Desbarats (1992b) modeled Le as a weighted spatial geometric average where the log permeabilities were weighed by the inverse square of their distance from the well.…”
Section: Model Comparisonmentioning
confidence: 99%
“…Where simplifjring assumptions concerning the spatial structure of the porous medium can be made and flows are uniform, upscaled permeability estimates are derived directly through analytical solutions (e.g., Gutjahr et al, 1978, Dagan, 1981Gelhar and Axness, 1983;Deutsch, 1989;Rubin and Gomez-Hernandez, 1990;Desbarats, 1992a). Where non-uniform flows are encountered a single effective permeability value can no longer be defined that is dependent soIely on the statistical properties of the permeability; rather, upscaling must explicitly account for the flow conditions unique to the problem (e.g., Ababou and Wood, 1990;Desbarats, 1992b;Indelman and Abramovich, 1994;Sanchez-Vila, 1997). For cases involving complicated heterogeneities andor flows numerical solutions to the upscaling problem are necessitated (e.g., White and Home, 1987;I Kitanidis, 1990;Durlofsky, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…To date, such efforts have relied on theoretical constructs coupled with mathematical modeling. One of the most widely recognized examples is the inverse distance squared weighting of heterogeneities by radial flow to a well [CaMwell and Parsons, 1945;Desbarats, 1992a]. Oliver [1990] used a perturbation approach to calculate the weighting function for permeability estimates derived from the semilog plot of drawdown versus time for nonsteady pump test data.…”
mentioning
confidence: 99%
“…In general, the different methods used in upscaling parameters like absolute permeability or transmissibility and relative permeability can be classified based on what is being upscaled and the technique used (see reviews by Smith, 1991;Desbarats, 1992;King et al 1995;Christie, 1996;Renard and Marsily, 1997;Chiles and Delfiner, 1999). In single-phase upscaling, the absolute permeability or transmissibility of the geologic model is upscaled, while in multi-phase in addition upscaling the absolute permeability or transmissibility, the relative permeabilities and capillary pressure are upscaled.…”
Section: General Upscaling Methodsmentioning
confidence: 99%